ALAT PERAGA ENGKLEK SEBAGAI UPAYA PENINGKATAN KEMAMPUAN MENGGALI PENGETAHUAN BARU SISWA - Ella Agustina; Imaniar Purbasari; Ristiyani Ristiyani (WASIS : Jurnal Ilmiah Pendidikan, 2020)
This study aims to describe the increase in the ability to explore new knowledge of students and teaching skills of teachers by using the engklek as media in grade IV SD IT Al-Hikmah Mayong.The class action research is carried out for two cycles, each cycle having two meetings and consisting of four stages, namely planning, acting, observing, and reflecting. Class IV research subjects at Al-Hikmah Mayong Elementary School with a total of 36 students. The independent variable in this study is the engklek as media, while the dependent variable is the ability to explore new knowledge. Data collection techniques using tests (written) and nontest include observation, interviews, and documentation. The analysis used is quantitative data analysis and qualitative data analysis.The results of the study showed that using a engklek as media could improve students ability to explore new knowledge and teaching skills. The ability to explore new knowledge of students has increased from cycle I 64% and cycle II to 92%. There is an increase in teacher teaching skills in the first cycle to get a success rate of 70% with enough categories, then in the second cycle to get a success rate of 94% with very good categories.